Mechanical properties of the semi-rigid subgrade of roads for the replacement cement with pyrolysis residues of oil sludge. (27th February 2023) - Ran, Wuping; Wang, Shuai; Shen, Xizhong; Wang, Yaqiang; Li, Yingqin
Highlights: Alternative mechanisms by the microporosity filling principle of oil film. Evaluation of mechanical properties of alternative materials by the TOPSIS method. 10% optimal alternative ratio of the pyrolysis residues to base cement. Improving stiffness of road base by cement replacement for the pyrolysis residues. Abstract: The pyrolysis residues of oil sludge, as the industrial solid waste of the oil extraction process, have a large output. There are also social and environmental problems of piling and pollution. Pyrolysis residues of oil sludge contain many active ingredients, which can partially replace cement and be added to road building materials for application. However, the mechanical properties are unknown for the replaced subgrade of roads. Through physicochemical and mechanical tests, the effect of the pyrolysis residues of oil sludge was studied based on the mechanical properties of road subgrade by replacing the proportion of the base cement of cement stabilized macadam (CSM) (10 %, 20 %, and 30 %). The recommended alternative ratio was proposed for replacing the cement of oil sludge stabilized macadam (COSM) base based on the correlation between mechanical indices and the technique for order preference by similarity to ideal solution (TOPSIS). The results suggest that an appropriate alternative ratio can optimally enhance the mechanical properties of the semi-rigid subgrade of conventional roads. Pyrolysis residues of oil sludge are easily excited in an alkaline environment, and its porous structure and carbon nanotube composition contribute to the combination with cementitious products to form a nail-carrying effect. Moreover, the hydration promotion effect on cementitious materials can increase the cleavage strength of materials. The replacement of cement with pyrolysis residues of oil sludge can enhance the mechanical properties of the material and increase the toughness of the material. The optimal moisture content of the material is positively correlated with the alternative ratio, and the maximal dry density is negatively correlated with the alternative ratio. The low alternative ratio is conducive to the increase of the early cementing effect of the material, and the high alternative ratio contributes to the increase of the later cementing impact of the material and the improvement of the later strength of the material. The range of alternative ratios to adjust the material to a reasonable range of the pressure-resistant resilience modulus was obtained as 12.6 %–31 %. The correlation analysis and technique for order preference by similarity to ideal solution method suggest that the reasonable alternative ratio of the pyrolysis residues of oil sludge is 10 %–30 % for the cement of stabilized macadam base, and the comprehensive mechanical properties of the 10 % replacement ratio are better than those of the control group. The results of this study can provide a reference for applying the pyrolysis residues of oil sludge in roads.